Experimental characterization of frp-masonry interface behaviour - Basílio, Ismael (2005)
Due to frp materials well known properties, restoration of historical heritage with such materials has become an attractive solution employed in structural rehabilitation, maintaining structural stability and avoiding unacceptable cracking or collapse. Specific knowledge concerning the structural behaviour of masonry structures strengthened with frp is quite scarce, which is a key issue when dealing with the strengthening of masonry constructions. This paper presents a set of experimental results on the characterization of the frp-masonry interface behaviour, carried out under direct shear loading. Brick masonry prisms were constructed and strengthened with frp strips bonded perpendicularly to bed joints. Different anchorage lengths and schemes, different frp materials and different masonry shapes were considered and studied. The experimental results are presented and discussed, particularly the variation of ultimate stress with the strengthening scheme and evolution of shear stress distribution along the anchorage length with stress level and strengthening scheme adopted.